2012
DOI: 10.14221/ajte.2012v37n4.2
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning: A Valuable Component of Pre-Service Teacher Education

Abstract: There is recognition that involvement in service-learning can impact positively on the development of pre-service teachers professionally, culturally and academically (Billig & Freeman, 2010;Anderson, 1998 (Jacoby, 1996;Kaye, 2004; Schoenfield, 2006;Scott, 2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 9 publications
11
53
0
19
Order By: Relevance
“…Examples include the use of service-learning programs in the development of active citizenship (James & Iverson, 2009), social awareness (Lavery, 2007), diversity (Glazier, Charpentier & Boone, 2011), multicultural education (Boyle-Baise, 2006), critical inquiry and reflection (Anderson, 2000) as well as social justice and special needs education (Chambers & Lavery, 2012). Such service-learning programs within teacher education usually aim to provide pre-service teachers with hands-on experiences in areas that are potentially outside their comfort zone (Colby, Bercaw, Clark & Galiardi, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include the use of service-learning programs in the development of active citizenship (James & Iverson, 2009), social awareness (Lavery, 2007), diversity (Glazier, Charpentier & Boone, 2011), multicultural education (Boyle-Baise, 2006), critical inquiry and reflection (Anderson, 2000) as well as social justice and special needs education (Chambers & Lavery, 2012). Such service-learning programs within teacher education usually aim to provide pre-service teachers with hands-on experiences in areas that are potentially outside their comfort zone (Colby, Bercaw, Clark & Galiardi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such service-learning programs within teacher education usually aim to provide pre-service teachers with hands-on experiences in areas that are potentially outside their comfort zone (Colby, Bercaw, Clark & Galiardi, 2009). These experiences often increase self-esteem in pre-service teachers, promote personal development and enhance a sense of social responsibility and personal competence (Anderson, 1998;Chambers & Lavery, 2012). What is less evident, however, is the use of service-learning programs as a means of preparing pre-service teachers for a teaching practicum or internship experience.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to highlight some particular and more widespread salient lines of work, such as its potential strategic force on teaching and learning (Batllé, 2013;Morin & Waysdorf, 2013;Russo, 2013), its relationship with local and communitary action (Becket, Refaei & Skutar, 2012), its link to values and social commitment teaching (Aramburuzabala, 2013;Boland, 2014), professional competences acquisition (Ferran & Guinot, 2012;Tejada, 2013), the impact on students (Lin, Wu, Wu, Pan, & Liao 2014;Waldner, McGorry, & Widener, 2012), the obstacles and limitations that these projects present (Crabtree, 2013;Páez & Puig, 2013) and their link with teacher training (Chambers & Lavery, 2012;Gleason & Violette, 2012;He & Prater, 2014). Another issue to be pointed out here is the rise that research on SL has in eastern regions such as China, Taiwan, Korea, Singapore, etc.…”
Section: Service-learning or When Methodology Becomes Actionmentioning
confidence: 99%
“…Teacher educators as their mentors can help pre-service teachers to reflect and link between teacher education curriculum and teaching practicum and thus enable them to "observe, interact, experiment and reflect in a supportive environment" (ibid.) Leadership can also be developed by encouraging pre-service teachers to take initiative, solve problems, work as a team and help others (Chambers & Lavery, 2012), which can possibly be embedded in teacher education curriculum and teaching practicum. Bond (2011) suggested that teacher educators should help preservice teachers aware of the various ways that they can lead in their future schools since the role of the teacher is multifaceted and extends beyond the classroom.…”
Section: Issues Of Developing Pre-service Teachers As Leadersmentioning
confidence: 99%